METODE SOSIODRAMA UNTUK MENINGKATKAN KEMAMPUAN MENYIMAK DONGENG DI MI MA’ARIF NU BAJONG KECAMATAN BUKATEJA KABUPATEN PURBALINGGA - Alfian Fendi Priyaji (Jurnal Penelitian Agama, 2015)
Abstract: The results showed that by applying the method of leaming Indonesian sociodramas on the short story material can enhance listening skills on Indonesian Language lesson of VB MI Ma'anif NU Bajong's students. This is indicated by an increase in value. The average value obtained grade students before giving the action was 61.5, while the percentage of students achieving mastery leaming is 15%. Keywords: Sociodrama Methods, Fairytale